2021
DOI: 10.1136/bmjopen-2020-046996
|View full text |Cite
|
Sign up to set email alerts
|

Stigma, displacement stressors and psychiatric morbidity among displaced Syrian men who have sex with men (MSM) and transgender women: a cross-sectional study in Lebanon

Abstract: BackgroundDisplaced Syrians face psychiatric morbidity often resulting from displacement-related stressors (eg, resource scarcity). Both men who have sex with men (MSM) and transgender women among the displaced Syrians are particularly vulnerable to mental health challenges given that they also often face stigma-related stressors (eg, discrimination).MethodsBetween January and December 2019 in greater Beirut, 258 Lebanese-born MSM and transgender women and 230 displaced Syrian MSM and transgender women were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…One study in Lebanon reported that 30% of recently migrated Syrian men experienced discrimination for being gay compared to 6% recently migrated Iraqi men or 8% Lebanese-born Palestinians ( p < 0.001) [ 59 ]. Another study in Lebanon found higher levels of sexual minority discrimination ( p < 0.01) and sexual minority assault ( p < 0.001) among displaced Syrians when compared to the non-displaced Lebanese population [ 57 ]. Several quantitative studies reported on employment and income.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study in Lebanon reported that 30% of recently migrated Syrian men experienced discrimination for being gay compared to 6% recently migrated Iraqi men or 8% Lebanese-born Palestinians ( p < 0.001) [ 59 ]. Another study in Lebanon found higher levels of sexual minority discrimination ( p < 0.01) and sexual minority assault ( p < 0.001) among displaced Syrians when compared to the non-displaced Lebanese population [ 57 ]. Several quantitative studies reported on employment and income.…”
Section: Resultsmentioning
confidence: 99%
“…A study on LGBTQ asylum seekers in Canada found that 72.4% of participants were employed, and in Lebanon the proportion of MSM refugees that were working was similar [ 58 , 59 ]. Two Lebanese studies reported that displaced participants received lower income compared to participants who hadn’t been displaced [ 57 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the overall mean age in the meta-analysis was 32 years. In the present meta-analysis, the first study to report the prevalence of depression in MSM was the article of Mills et al [ 55 ], and the most recent study which measured the prevalence of depression in MSM was the article of Clark et al [ 32 ]. The highest number of studies was related to 2018 with 14 articles [ 26 , 31 , 34 , 46 , 47 , 50 , 58 , 60 , 62 , 69 , 71 , 77 , 84 , 89 ] and 2017 with 11 articles [ 28 , 30 , 38 , 40 , 41 , 43 , 54 , 56 , 67 , 70 , 73 ].…”
Section: Resultsmentioning
confidence: 99%